A Solid‐State Reference Electrode Based on a Self‐Referencing Pulstrode. Issue 6 (19th December 2019) - Gao, Wenyue; Zdrachek, Elena; Xie, Xiaojiang; Bakker, Eric
Abstract: The design of solid‐state reference electrodes without a liquid junction is important to allow miniature and cost‐effective electrochemical sensors. To address this, a pulse control is proposed using an Ag/AgI element as reliable solid‐state reference electrode. It involves the local release of iodide by a cathodic current that is immediately followed by an electromotive force (EMF) measurement that serves as the reference potential. The recapture of iodide ions is achieved by potentiostatic control. This results in intermittent potential values that are reproducible to less than one millivolt (SD=0.27 mV, n =50). The ionic strength is shown to influence the activity coefficient of released iodide in accordance with the extended Debye–Hückel equation, resulting in a predictable change of the potential reading. The principle is applied to potentiometric potassium detection with a valinomycin‐based ion‐selective electrode (ISE), demonstrating a completely solid‐state sensor configuration. Abstract : Pulstrode ! A solid‐state reference electrode principle is proposed that relies on a self‐referencing Ag/AgI element. An applied current pulse generates iodide ions that dictate the reference electrode potential, which are subsequently recaptured.